Epigenetic modulation of glucocorticoid receptors in posttraumatic stress disorder - Labonté, B (Nature Publishing Group, 2014)
Some individuals suffering from posttraumatic stress disorder (PTSD) exhibit lower basal salivary cortisol and higher glucocorticoid receptor (GR) sensitivity. Recent studies suggest that epigenetic mechanisms regulate the activity of cortisol and GR. As a means to combine and cross-validate those findings, we compared cortisol, GR expression and promoter methylation levels in peripheral T lymphocytes of healthy controls versus individuals endorsing a diagnosis of lifetime PTSD. Thirty subjects with lifetime (current or remitted) PTSD and 16 subjects never exposed to trauma were recruited. Salivary cortisol was collected at six time points over the course of a single weekday and analyzed utilizing a time-resolved fluorescence immunoassay. GR expression (GR(total), 1(B), 1(C), 1(F) and 1(H)) was measured by quantitative RT-PCR. DNA methylation levels in human glucocorticoid receptor (hGR) 1(B) and 1(C) variant's promoter were quantified by epityper in T lymphocytes isolated by magnetic-assisted cell sorting. Individuals with lifetime PTSD have lower morning cortisol release, higher mRNA expression of hGR(total), 1(B), and 1(C) and lower overall methylation levels in hGR 1(B) and 1(C) promoters. Cortisol levels were inversely correlated with hGR 1(B) mRNA expression. Moreover, overall and CpG site-specific methylation levels were inversely correlated with hGR(total) and 1(B) mRNA expression. There was no difference between current and remitted PTSD across cortisol, GR expression mRNA and DNA methylation data. Traumatic events induce DNA methylation alterations in distinct promoters of hGR with transcriptional modifications that associate with hypoactive hypothalamus-pituitary-adrenal axis in individuals with PTSD. Our results also point toward an important role of hGR 1(B) variant in PTSD.